2022
DOI: 10.1097/qad.0000000000003158
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of DREAMS: using data for continuous program improvement

Abstract: The DREAMS (Determined, Resilient, Empowered, AIDS-Free, Mentored, and Safe) Partnership, a public-private partnership launched by the United States President's Emergency Plan for AIDS Relief (PEPFAR), represents the largest investment in comprehensive HIV prevention for adolescent girls and young women (AGYW) ever made in a single global initiative. This paper describes the evolution of programming over time using the triangulation of multiple data sources to develop and refine an impactful program, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…This investment must include continuous monitoring and evaluation to determine the impact on HIV diagnoses among AGYW using multiple sources of data for timely programmatic improvements, especially given the complexities of implementing programming that combines biomedical, structural, and behavioral interventions. The analyses in this article complement others included in this supplement issue that directly speak to implementation improvements [29] and changes in secondary outcomes [30,31], and changes in incidence [31]. Our findings align with similar published modeling in Lesotho that found declines in new HIV diagnosis rates at ANC in DREAMS SNUs were greater than in non-DREAMS SNUs [32].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This investment must include continuous monitoring and evaluation to determine the impact on HIV diagnoses among AGYW using multiple sources of data for timely programmatic improvements, especially given the complexities of implementing programming that combines biomedical, structural, and behavioral interventions. The analyses in this article complement others included in this supplement issue that directly speak to implementation improvements [29] and changes in secondary outcomes [30,31], and changes in incidence [31]. Our findings align with similar published modeling in Lesotho that found declines in new HIV diagnosis rates at ANC in DREAMS SNUs were greater than in non-DREAMS SNUs [32].…”
Section: Discussionsupporting
confidence: 84%
“…DREAMS has demonstrated that continuous data analyses and program course corrections based on quantitative and qualitative information can result in improvements in both implementation and outcomes. Two years ago, PEPFAR conducted a similar predictor analysis, revealing that a greater number of implementing partners, partial geographic coverage within a SNU, and implementation in urban areas was associated with smaller declines in new diagnoses [34]. In response, DREAMS guidance was revised to encourage consolidation and coordination of partner efforts and implementation across full SNUs [35].…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…Contextual interventions include community-based services that cannot necessarily be delivered discretely to DREAMS participants but can be prioritized in specific communities (e.g., with higher HIV burdens) or tailored to specific populations (e.g., male partners). 15 In Zambia, contextual interventions included community mobilization and norms-changing activities focused on violence prevention and gender equity.…”
Section: Dreams Rollout and Scale-up In Zambiamentioning
confidence: 99%
“…IP organizations delivering individual DREAMS interventions are integrated primarily through formal referral mechanisms, whereby implementing staff must actively link (through accompaniment or individual case management) AGYW to services offered by other IP organizations within the DREAMS Partnership. 15 Individual interventions included in the primary service package are also delivered through community-based platforms called DREAMS centers or venues located within communities where AGYW congregate and participate in DREAMS-sponsored activities and services.…”
Section: Dreams Rollout and Scale-up In Zambiamentioning
confidence: 99%
See 1 more Smart Citation